Pengaruh Gaya Kepemimpinan Konsiderasi, Subjektif Diagnostik, Subjektif Interaktif Terhadap Kejelasan Tujuan - Riski Hernando; Rezi Abdurrahman; Eko Prasetyo (Universitas Negeri Padang, 2020)
This study aims to examine the effect of consideration leadership on goal clarity. This study also examines the mediation of subjective diagnostic and subjective interactive on the relationship between initiation structure leadership and evaluation fairness. Sample in this study use 152 subordinates in merchandising, services and manufacturing business. Data processed using structural equation modeling with WarpPLS 3.0 software. Data were collected using a questionnaire with hand delivery system technique. The results of this study indicate that consideration leadership influences goal clarity. However, the only one mediation variable support the hypotheses in this study, and the other one do not support the hypotheses. Keywords: Goal Clarity; Consideration Leadership; Subjective Diagnostic; Subjective Interactive